Parental involvement in home preparation – “COVID-19 or not, I still need to help my child” - Petrů Puhrová, Barbora (Acta Paedagogica Vilnensia, 2024)
The study deals with parental involvement in the child’s home preparation. The qualitative research with parents of primary school pupils showed the parental homework attitudes and conditions, and reflected changes and strategies in home preparation during pandemic times. Regardless of any pandemic, the results showed differences in homework management; nevertheless, parental help directs to achieve independence and responsibility for the child’s learning, no matter the pandemic.
Keywords: parental involvement; homework; primary school education; home preparation for schooling; COVID-19